1992
DOI: 10.1039/ft9928803375
|View full text |Cite
|
Sign up to set email alerts
|

Modified zinc oxide absorbents for low-temperature gas desulfurisation

Abstract: The hydrogen sulfide absorption capacity of zinc oxide doped with first-row transition-metal oxides (ca. 5% metal oxide loading) has been determined using a pulse reactor. The doped oxides were prepared either by impregnation of ZnO with t h e transition-metal nitrates or by coprecipitation of t h e transition-metal and zinc nitrates with ammonium/sodium carbonate. These absorbent precursors were then calcined to give the mixed oxides.Transmission electron microscopy studies of t h e impregnated and calcined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 6 publications
5
61
1
Order By: Relevance
“…At 22°C, the breakthrough capacity and saturation capacity of PEI(50)/SBA-15 were 0.79 and 1.98 mmol-H 2 S/g-sorb, respectively, which were about 20 times as large as those at 75°C (0.037 and 0.11 mmol-H 2 S/g-sorb, respectively). This saturation capacity is significantly higher than that reported in literature for the amine-grafted MCM-48 adsorbent [31] and is in the same magnitude as those reported for the mixed metal oxides [13,[15][16][17][18][19][20] at the comparable sorption temperature. In our previous study, it was also found that for the sorption of CO 2 on a PEI/MCM-41 sorbent, the sorption capacity increased with increasing temperatures from 50 to 75°C and then, decreased with continuous increase in temperatures [26].…”
Section: Effect Of Sorption Temperaturesupporting
confidence: 61%
See 1 more Smart Citation
“…At 22°C, the breakthrough capacity and saturation capacity of PEI(50)/SBA-15 were 0.79 and 1.98 mmol-H 2 S/g-sorb, respectively, which were about 20 times as large as those at 75°C (0.037 and 0.11 mmol-H 2 S/g-sorb, respectively). This saturation capacity is significantly higher than that reported in literature for the amine-grafted MCM-48 adsorbent [31] and is in the same magnitude as those reported for the mixed metal oxides [13,[15][16][17][18][19][20] at the comparable sorption temperature. In our previous study, it was also found that for the sorption of CO 2 on a PEI/MCM-41 sorbent, the sorption capacity increased with increasing temperatures from 50 to 75°C and then, decreased with continuous increase in temperatures [26].…”
Section: Effect Of Sorption Temperaturesupporting
confidence: 61%
“…In the range of 25-100°C, Carnes and Klabunde [13] found the activity of nanocrystalline metal oxides prepared by a sol-gel method decreased in the order of ZnO [ CaO [ Al 2 O 3 [ MgO. In order to improve the adsorption capacity at low temperature, many metal oxides have been tested and investigated, which includes ferric oxyhydroxides (FeOOH) [14], iron, copper, and cobalt doped zinc oxide [15], cobalt-zinc-aluminum oxides [16], iron-zinc and iron-cobalt mixed oxides [17,18], and Zn-Ti-based oxides [19,20]. However, the regeneration of the spent metal-oxide-based sorbents needs to be conducted usually at high temperature ([450°C) in the presence of O 2 .…”
Section: Introductionmentioning
confidence: 98%
“…For instance, the best-performing samples reported so far are activated carbons with capacities up to 300 mg g À1 . [6] For zinc oxide, the values range between 1 and 25 mg g À1 , [9] whereas for sludge-based materials it is between 18 and 33 mg g À1 . [12,13] Moreover, clays can adsorb up to 50 mg g À1 hydrogen sulfide.…”
Section: Resultsmentioning
confidence: 99%
“…Of the several mixed-metal oxide sorbents investigated, ZnO-FqO,, ZnO-TiO,, CuO-A1203, CuO-Fe,O,, CuO-Fq0,-Al,O,, Coo-TiO, (Fahara andGarder, 1980;Grindley and Steinfeld, 1981, 1982, 1983, 1984Grindley 1986;Grindley, 1989, Anderson andHill, 1988;Focht et al, 1988;Flytzani-Stephanopoulos et al, 1987Flytzani-Stephanopoulos and Jothimwugesan, 1990;Jothimurugesan and Harrison, 1990;Lew et al, 1989Lew et al, , 1992% 1992bSriwardane and Poston, 1990;Tamhanker et al, 1986;Ayala et al, 1991;Gangwal et al, 1988;Patric et al, 1989;Woods et al, 1990, Baird et al, 1992Jain et al, 1993), only zinc-and iron based sorbents have emerged as having good potential for application as regenerable hot-gas desulfurization agents in IGCC systems. Although the feasibility of removing H2S to very low levels (e.g., <50 ppmv) from coal gases has been shown to be viable in most studies of mixed-metal oxides, the major limitations for large scale use of mixed-metal oxides is the lack of chemical and mechanical stability under reducing gas atmospheres or the difficulty of regeneration over many cycles.…”
Section: Portionsmentioning
confidence: 99%